2016
DOI: 10.1002/pbc.26399
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of high‐dose 131I‐metaiodobenzylguanidine treatment into killer immunoglobulin‐like receptor/HLA‐ligand mismatched haploidentical stem cell transplantation for children with neuroblastoma who failed tandem autologous stem cell transplantation

Abstract: Our results suggest that the incorporation of HD-MIBG treatment in haplo-SCT and the use of BX haplotype donors might improve outcome, but this approach is currently limited by unacceptable GVHD. Further work focused on enhancement of GVT effects in relapsed neuroblastoma should be coupled with efforts to reduce GVHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…RT dose and volume were determined according to previous RT prior to relapse/progression. 6 7 A detailed review of the clinical data was performed to ascertain the presenting features, degree of surgical resection, pathology, chemotherapy regimen, RT, the response to salvage treatment, and any events (relapse/progression, second malignancy, treatment-related mortality, and death).…”
Section: Methodsmentioning
confidence: 99%
“…RT dose and volume were determined according to previous RT prior to relapse/progression. 6 7 A detailed review of the clinical data was performed to ascertain the presenting features, degree of surgical resection, pathology, chemotherapy regimen, RT, the response to salvage treatment, and any events (relapse/progression, second malignancy, treatment-related mortality, and death).…”
Section: Methodsmentioning
confidence: 99%
“…HaploHSCT has been studied as a potential treatment modality exploiting the graft‐versus‐tumor effect from NK‐cell alloreactivity . Initial experience with haploHSCT highlighted the need to minimize TRM due to GvHD and infection associated with GvHD treatment . Ex vivo engineering of stem cell graft, initially by CD34 positive selection, has evolved to become a feasible tool to mitigate GvHD in haploHSCT, with the disadvantage of delayed immunoreconstitution and depleted alloreactive NK cells .…”
Section: Discussionmentioning
confidence: 99%
“…Various graft manipulation protocols have since been designed to improve the outcome in patients undergoing haploHSCT . The literature about haploHSCT in NB is scarce and limited to small series and case reports (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroblastoma cells have been reported to have decreased class I HLA expression, which suggests that NK cell therapy may be effective in killing neuroblastoma cells [16]. Our previous study showed that KIR/HLA-ligand mismatched haplo-SCT might improve outcomes in children with recurrent neuroblastoma; however, most relapse/progression occurred in the early post-transplant period, suggesting the need for further effective treatment to prevent early relapse after haplo-SCT [17].…”
Section: Introductionmentioning
confidence: 99%